Supine plasma NE predicts the pressor response to droxidopa in neurogenic orthostatic hypotension - Palma, Jose-Alberto (Neurology, 2018)
OBJECTIVE: To test whether the plasma levels of norepinephrine (NE) in patients with neurogenic orthostatic hypotension (nOH) predict their pressor response to droxidopa. METHODS: This was an observational study, which included patients with nOH. All patients had standardized autonomic function testing including determination of venous plasma catecholamine levels drawn through an indwelling catheter while resting supine. This was followed by a droxidopa titration with 100 mg increments in successive days until relief of symptoms, side effects, or the maximum dose of 600 mg was reached. No response was defined as an increase of <10 mm Hg in systolic blood pressure (BP) after 3-minute standing 1 hour after droxidopa administration. Nonlinear regression models were used to determine the relationship between BP response and plasma NE levels. RESULTS: We studied 20 patients with nOH due to Parkinson disease, pure autonomic failure, multiple system atrophy, or autoimmune autonomic neuropathies. Their supine plasma NE levels ranged from 44 to 850 pg/mL. Lower supine plasma NE levels were associated with greater pressor effect 1 hour after dose (R(2) = 0.49) and higher standing BP (R(2) = 0.45). Patients with no pressor response to droxidopa had higher NE levels (382 ± 100 vs 115 ± 20 pg/mL, p = 0.0014). A supine NE level of <219.5 pg/mL had 83% sensitivity and 93% specificity to predict a pressor response (area under the curve = 0.95, p = 0.0023). CONCLUSIONS: In patients with nOH, lower supine resting plasma NE levels are associated with a greater pressor effect of droxidopa treatment. This finding should help identify patients with nOH most likely to respond to standard doses of droxidopa. CLASSIFICATION OF EVIDENCE: This study provides Class I evidence that lower supine plasma NE levels accurately identify patients with nOH more likely to have a greater pressor effect from droxidopa.